Breastfeeding duration and the risk of systemic juvenile idiopathic arthritis: a cross-sectional study - Luo, Qiang; Zhang, Hui; Wu, Xinlin; Wei, Xiaoqiong; Tang, Xuemei (Frontiers in Nutrition, 2025)
BackgroundSystemic juvenile idiopathic arthritis (sJIA) is an autoinflammatory subtype of JIA with distinct immunopathogenic mechanisms. Early-life nutritional exposures such as breastfeeding may influence immune development and inflammatory disease risk, yet evidence in sJIA remains limited. Therefore, this study aimed to examine the association between breastfeeding duration and the likelihood of developing sJIA versus non-sJIA, and to assess whether systemic inflammatory markers mediate this relationship.MethodsIn this cross-sectional study, we included 450 children diagnosed with JIA from 2018 to 2024 at Children’s Hospital of Chongqing Medical University. Breastfeeding duration was retrospectively collected, and patients were classified into sJIA and non-sJIA groups. Multivariable logistic regression and restricted cubic spline models were used to assess the association between breastfeeding duration and the risk of sJIA. Mediation analysis was conducted to quantify the indirect effects of inflammatory mediators on this association.ResultsAmong 450 patients with JIA, those with sJIA (n = 150) had significantly shorter breastfeeding duration than non-sJIA patients (n = 300) (mean 6.3 vs. 9.1 months, p < 0.001). sJIA cases also showed higher levels of inflammatory markers, including neutrophil count, C-reactive protein (CRP), erythrocyte sedimentation rate, and white blood cell (WBC). Multivariable logistic regression confirmed that shorter breastfeeding duration was independently associated with higher odds of sJIA (adjusted OR = 0.86; 95% CI: 0.77–0.96; p = 0.009). Restricted cubic spline analysis revealed a non-linear inverse relationship between breastfeeding duration and sJIA likelihood, with an inflection point near 7.5 months. Mediation analysis indicated that neutrophil count, WBC count, and CRP partially mediated the relationship between breastfeeding and sJIA, accounting for 26.5, 25.8, and 12.4% of the total effect, respectively.ConclusionShorter breastfeeding duration is associated with a higher probability of sJIA, and this relationship may be partially mediated by systemic inflammatory status. These findings highlight the potential role of early-life nutritional exposures in promoting autoinflammatory disease expression and support further prospective investigations.